2016
DOI: 10.17221/8879-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of stone loach (Barbatula barbatula) and hybrids between sterlet (Acipenser ruthenus) and beluga (Huso huso) to cyprinid herpesvirus 3

Abstract: Cyprinid herpesvirus 3 also known as koi herpesvirus is a causative agent of highly contagious disease (koi herpesvirus disease) and can cause significant losses in fish stocks. The disease is restricted to koi and common carp, but recent investigations have shown that other cyprinids as well as non-cyprinid species are asymptomatically susceptible to this virus and can play either a role as a potential carrier or can contribute to biological conservation of this virus. The susceptibility of two non-target spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
(18 reference statements)
0
3
0
Order By: Relevance
“…Only one of them is officially recognized by the ICTV: acipenserid herpesvirus 2 (AciHV-2), which is included in the genus Ictalurivirus [31]. Non-sturgeon-specific Alloherpesviridae have also been reported [34,35].…”
Section: Herpesvirusesmentioning
confidence: 99%
See 1 more Smart Citation
“…Only one of them is officially recognized by the ICTV: acipenserid herpesvirus 2 (AciHV-2), which is included in the genus Ictalurivirus [31]. Non-sturgeon-specific Alloherpesviridae have also been reported [34,35].…”
Section: Herpesvirusesmentioning
confidence: 99%
“…Although not specifically a pathogen of sturgeon, Cyprinid Herpesvirus-3 (CyHV-3) or Koi Herpesvirus (KHV) has been reported in Acipenseridae. The two documented cases concern Atlantic sturgeon (A. oxyrhynchus), Russian sturgeon (A. gueldenstaedtii) [34] and a Bester hybrid (A. ruthenus x H. huso) [35]. Since only viral DNA was found, there is not enough evidence to support the infection hypothesis, as indicated by the World Organization for Animal Health (OIE) manual ("species with incomplete evidence for susceptibility") [66].…”
Section: Cyprinid Herpesvirus 3 (Cyhv3)mentioning
confidence: 99%
“…According to Pospichal et al (2016) the hybrid between sterlet and beluga seems to be susceptible to cyprinid herpesvirus 3, but the authors could not prove that they can transfer this virus to naïve koi. Also, Kempter et al (2009) reported that Atlantic sturgeon and Russian sturgeon are susceptible to CyHV-3.…”
Section: Cyprinid Herpesvirus-3 (Cyhv-3)mentioning
confidence: 99%